2015
DOI: 10.1007/s00038-015-0649-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of digital media on health: children’s perspectives

Abstract: Qualitative methodology helps to understand what children's perspectives are concerning the impact of digital media on health. We recommend future studies focused on average technology users and low technology users to determine whether average levels of technology usage relate to health problems of children. Parents and teachers should also be informed about the possible physical and mental health issues associated with children's average usage of technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 30 publications
1
23
0
5
Order By: Relevance
“… 14 Similarly, Smahel et al reported that children with internet addiction encountered problems including nutrition disorders. 15 Similarly, we found that there is a positive relationship between the increase in the duration of digital gaming and risky eating habits.…”
Section: Discussionsupporting
confidence: 59%
“… 14 Similarly, Smahel et al reported that children with internet addiction encountered problems including nutrition disorders. 15 Similarly, we found that there is a positive relationship between the increase in the duration of digital gaming and risky eating habits.…”
Section: Discussionsupporting
confidence: 59%
“…In Smahel and colleagues' [28] research, digital media including internet use and technology impacted physical and mental health problems to children. It is presumed that female students who have a negative mental state and strong emotional stress due to their personal conditions, including their familial environment, have a great risk to suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the impact of exposure time to digital screens on children demonstrate that the chances of symptoms increase after 2-4 h of exposure (13,14). A qualitative research article presented results from focus groups and interviews conducted with 368 children between 9 and 16 years old in nine European countries on what they perceived as being potentially negative or problematic while using the internet and technology (15). Children reported a variety of eye problems, such as their eyes hurting, eyestrain, and needing to wear glasses due to prolonged internet usage.…”
Section: Negative Effects Of Videogaming Problematic Internet Use Amentioning
confidence: 99%